Creating Mobile Games - Hamer, Carol (Apress, 2012)
When people ask me what I do, in addition to telling them I can show them: I can pull out my cell phone and demonstrate some of the games I’ve written for it. It’s a great time to be a software developer because a pastime that’s so much fun—writing games for cell phones and mobile devices—is now a huge growth industry. The number of cell phones worldwide is well over 2 billion, dwarfing the market of other high-tech items such as personal computers. The number of Java-enabled cell phones is in the hundreds of millions, and, by some counts, the number may already be over a billion. And since cell phones are naturally a personal-use device, many of these users will want to use their phones for fun and entertainment, and you can tap into that market with Java Micro Edition games. If you’re already a software engineer with lots of experience in Java Standard Edition and/or Java Enterprise Edition, learning to use Java Micro Edition isn’t too hard. And if you have only a basic knowledge of programming in Java, Java ME is a fine place to start. The main differences you encounter in your day-to-day programming are the limitations of the devices involved and the differences from one device to the next